The Review of Evidences That al-Tabarsi Used in The Argument of Recitations - Saylan, Nesrisah (Cumhuriyet Univ, Fac Theology, 2019)
al-Tabarsi is one of the glossators in the Shi'ah gloss tradition in the second middle period or first sagacity period. al-Tabarsi who had a wide knowledge in the various knowledge branches was mentioned as a glossator, narrator of Mohammad's all sayings, deeds and approvals and scribe. One of compilations that al-Tabarsi wrote it in the field of gloss is Macmau-l-bayan fi tafsiri-l-Qur'an. The glossator who widely included the recitations in this work used some evidence related to their averment while he was reporting the recitations, and he made the recitations' justification in the framework. The averment is a science which determines the correct recitations as distinguishing the correct one of recitation's differences from the deficient one, and which founds an aspect of the correct category with all the other transferred and linguistic arguments of recitation in the predilection besides the imputation, the formal Qur'an. Al-Tabarsi first mentioned the recitations under the subtitle of recitation related to the verses in each sura and then transferred the argument of recitations with the term of argument. So the glossator applied to give evidence on them with the linguistic and transferred arguments in each of the parts that the recitations were nearly mentioned. He mentioned the imputation, the Qur'an lettering, verse, hadith, companion and natural people's readings. He used Arabic poetry, Arabic idiom, dialect, grammar and syntax rules for the linguistic arguments. In this study, the evidences which were used in the recitations' averment are reviewed in the sample of al-Tabarsi's gloss in the name of Majmau-l-bayan.
Tabersî'nin kiraatlerin hüccetinde kullandiği delillerin I?ncelenmesi
Keywords: Tafsir; Recitation; Shi'a; al-Tabarsi; Argument